In Vitro Production of Virulence Factors and Antifungal Susceptibility Pattern of Aspergillus Isolates from Clinical Samples in a Tertiary Care Center - Bavadharani, Sukumar; Premamalini, Thayanidhi; Karthika, Kanagasabapathi; Kindo, Anupma Jyoti (Journal of Laboratory Physicians, 2022)
Objectives This study was aimed to investigate the association between virulence factors and antifungal susceptibility pattern among Aspergillus species.Materials and Methods This study was carried out in the Department of Microbiology, from May 2018 to June 2019. A total of 52 Aspergillus isolates obtained from various clinical samples were speciated based on microscopic identification by lacto phenol cotton blue (LPCB) mount and slide culture technique. The production virulence factors such as biofilm, lipase, phospholipase, amylase, and hemolysin were detected using standard phenotypic methods with Aspergillus niger ATCC (American Type Culture Collection) 6275 as the control strain. Antifungal susceptibility patterns of all Aspergillus isolates to amphotericin B, itraconazole, voriconazole, and posaconazole were evaluated in line with the Clinical Laboratory Standards Institute (CLSI) M38-A2 guidelines.Results The percentage of resistance was the highest in itraconazole (48.08%), followed by amphotericin B (28.85%) and voriconazole (9.62%). All amphotericin B-resistant isolates produced biofilm, itraconazole-resistant isolates exhibited phospholipase activity, and voriconazole-resistant isolates produced biofilm and demonstrated phospholipase and hemolytic activities. Regardless of the virulence factors produced, all isolates were susceptible to posaconazole.Conclusion Understanding the relationship between virulence factors and antifungal resistance aids in the development of new therapeutic approaches involving virulence mechanisms as potential targets for effective antifungal drug development.
Keywords: Antifungal susceptibility; Aspergillus species; biofilm; phospholipase; virulence factors